2022
DOI: 10.1111/ajt.17175
|View full text |Cite
|
Sign up to set email alerts
|

ABO-adjusted calculated panel reactive antibody (cPRA): A unified metric for immunologic compatibility in kidney transplantation

Abstract: Implementation of the kidney allocation system in 2014 greatly reduced access disparity due to human leukocyte antigen (HLA) sensitization. To address persistent disparity related to candidate ABO blood groups, herein we propose a novel metric termed "ABO-adjusted cPRA," which simultaneously considers the impact of candidate HLA and ABO sensitization on the same scale. An ethnic-weighted ABO-adjusted cPRA value was computed for 190 467 candidates on the kidney waitlist by combining candidate's conventional HLA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
7
1
Order By: Relevance
“…of each blood group also varies considerably between different localities and ethnic groups. 18,26 Contrast to the USA where blood groups A and B accounts for 37% and 12% in the donor pool, our local data showed that blood groups A and B each accounts for approximately 25% of the donors. Another difference is the higher percentage of blood group AB in Hong Kong than in the USA (7% vs. 3.5%).…”
Section: F I G U R Econtrasting
confidence: 80%
See 4 more Smart Citations
“…of each blood group also varies considerably between different localities and ethnic groups. 18,26 Contrast to the USA where blood groups A and B accounts for 37% and 12% in the donor pool, our local data showed that blood groups A and B each accounts for approximately 25% of the donors. Another difference is the higher percentage of blood group AB in Hong Kong than in the USA (7% vs. 3.5%).…”
Section: F I G U R Econtrasting
confidence: 80%
“…With a population of 7.3 million (91.6% were Chinese), over 95% of the kidney donor pool in the ORTS of Hong Kong are of Chinese ethnicity, and due to such ethnic predominance the HLA allele/haplotype frequencies differ significantly from other populations and transplant programs 29,36–40 . Add to that, the phenotypic frequency of each blood group also varies considerably between different localities and ethnic groups 18,26 . Contrast to the USA where blood groups A and B accounts for 37% and 12% in the donor pool, our local data showed that blood groups A and B each accounts for approximately 25% of the donors.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations